2015
DOI: 10.7314/apjcp.2015.16.6.2473
|View full text |Cite
|
Sign up to set email alerts
|

Dendrosomal Curcumin Inhibits Metastatic Potential of Human SW480 Colon Cancer Cells through Down-regulation of Claudin1, Zeb1 and Hef1-1 Gene Expression

Abstract: Colon cancer is one of the leading causes of cancer-associated death worldwide. The prognosis for advanced colorectal cancers remains dismal, mainly due to the propensity for metastatic progression. Accordingly, there is a need for effective anti-metastasis therapeutic agents. Since a great body of research has indicated anticancer effects for curcumin, we investigated the effects of dendrosomal curcumin (DNC) on cellular migration and adhesion of human SW480 cells and possible molecular mechanisms involved. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…We have demonstrated that by employing our dendrosome nano-particles in vitro, the solubility of FC thereby its anti-proliferation effect on cancer cells could be improved. Dendrosomes are neutral, covalent, selfassembled, biodegradable and spherical nano-particles and their exceptional capabilities have been shown in safely delivering genes and herbal compounds into the different cell lines (Sarbolouki et al, 2000;Sadeghizadeh et al, 2008;Mashinchian et al, 2010;Babaei et al, 2012, Dehghan Esmatabadi et al, 2015. Current work covers the study of anti-proliferation and apoptotic effects of DFC compared to FC.…”
Section: Anti-proliferative and Apoptotic Effects Of Dendrosomal Farnesiferol C On Gastric Cancer Cellsmentioning
confidence: 99%
“…We have demonstrated that by employing our dendrosome nano-particles in vitro, the solubility of FC thereby its anti-proliferation effect on cancer cells could be improved. Dendrosomes are neutral, covalent, selfassembled, biodegradable and spherical nano-particles and their exceptional capabilities have been shown in safely delivering genes and herbal compounds into the different cell lines (Sarbolouki et al, 2000;Sadeghizadeh et al, 2008;Mashinchian et al, 2010;Babaei et al, 2012, Dehghan Esmatabadi et al, 2015. Current work covers the study of anti-proliferation and apoptotic effects of DFC compared to FC.…”
Section: Anti-proliferative and Apoptotic Effects Of Dendrosomal Farnesiferol C On Gastric Cancer Cellsmentioning
confidence: 99%
“…A lipophilic analog of curcumin, Dimethoxy curcumin, inhibits the growth of CRC by downregulating survivin and upregulating E‐cadherin of CRC cells (Chen et al, ). Dendrosomal curcumin prevents metastatic potential of CRC cells via downregulation of cell adhesion proteins including Hef‐1, Zeb‐1, and Claudin‐1 (Dehghan Esmatabadi et al, ). Similarly, Su et al indicated that curcumin suppresses invasion and metastasis of CRC via modulation of NF‐κB and downregulation of COX‐2 and matrix metalloproteinase‐2 (MMP‐2) expressions (Su, Chen, Lin, Wu, & Chung, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Dehghan Esmatabadi, et al (2015), the effects of dendrosomal curcumin (DNC) on cellular migration and adhesion of human SW480 colon cancer cells were searched and DNC was found to inhibit metastasis by causing a decrease in mRNA levels of some proteins including Claudin 1, Hef 1 and Zeb 1 (Dehghan Esmatabadi et al, 2015). Tan et al (2004) showed that expression and dispersion of Claudin 1 is related with dissociation of the pancreatic cancer cells (Tan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%